THE VILLAGE FINANCIAL MANAGEMENT ACCOUNTABILITY: AN INVESTIGATION INTO VILLAGES IN THE RUPIT DISTRICT - Huzadi; Rita Martini; Sarikadarwati; Yuli Antina Aryani; Margaretha Esiakhe Lokobal (Universitas La Tansa Mashiro, 2026)
This study looks at how Apparatus Competence, the use of Information Technology, and the Government Internal Control System (SPIP) affect the accountability of village financial management in Rupit District. The study included 16 villages located in Rupit District. The study used a purposive sampling method and included 64 participants in total. Data was gathered by giving questionnaires directly to the people who responded. The data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEMPLS) method, and the analysis was done with the help of SmartPLS version 4 software. The findings show that the skill level of the equipment has a positive and important influence on how responsible the village's financial management is. Using information technology has a positive and important impact on how villages manage their finances responsibly. The Government Internal Control System has a good and important impact on how accountable village financial management is. At the same time, the ability of the apparatus, the use of information technology, and the government's internal control system all have a positive and important impact on how accountable village financial management is. The R² value is 74.3%, which means that 74.3% of how well the village financial management is handled can be explained by the competence of the staff, the use of information technology, and the government's internal control system